Peranan Dan Kontribusi Jasa Angkutan Kereta Api Terhadap Perekonomian Indonesia (Studi Penerapan Analisis 1-0 2005) - Siswanto, Adrianus Dwi (Warta Penelitian Perhubungan, 2010)
As a developing countn;, transport sector, particulnrly road transport plm;s an important role. Ihisstudy examines the role of the railwm; senrices to the Indonesian econorm;. I11e metlwdologtj used isinput - output analysis using Input - Output Tnble 2005.Tire study shows that tire railway seruices occupi; the last place that contributed to the Indonesianeconomy, which is 0.05 percent. This mlue is tire lowest compared with otlrer transport sectors.While contributions from the output of railway· transport senrices were occupijng last place in theoutput contribution to the econorm; in Indonesia, 11rith 0.08 perrent.Tire value of final demand sectors of the railwm; senrices are higher than tire intermediate demandcaused ln.j the sector is the sen1ices sector. f 11 tenns of linknges, tlie milwm; senrices sector 11£15 a highbackward linkages. Tizis indiaztes tluzt this sector is i111portmzt for actizrities in the upstream.From the value of railwm; transportation senrices output multiplier has tire highest value comparedto other sectors. Mining sector, many use the train senrices to transport and distribute the results oftire mine. Furtliermore, multiplier value of reuenue from railwm; transport sennces shows that forevery increase in final demand for railwm; senrices amounted to USO 1 million 11rill increase tire totalrevenue of tire entire economy of 0.8363 million tinies before or 0.8363 million rezrnue.